Observe and make a call: football referee's assessment is context sensitive. (1st November 2020) - Carvalho, V.; Esteves, P.T.; Nunes, C.; Araújo, D.; Helsen, W.F.; Travassos, B.
ABSTRACT: This study aimed to understand the level of agreement between different methods of observation and assessment of the performance of football referees carried out by Referee Match Observers: (i) live; (ii) live + video and (iii) single video. A total of 34 Referee Match Observers from the 1st category of the Portuguese Football Association (FA) participated in the study. The evaluation followed the official assessment guidelines according to three criteria: (a) general evaluation; (b) game difficulty and general performance; and (c) disciplinary actions and game management. Results revealed different levels of agreement in the judgement and evaluation of the referee's performance between live, live + video and video only. Results suggest that the combination of live and video analysis allow RMOs to be more perceptually attuned to the events that convey relevant information to better support the assessment of referee's performance. This work offers evidence for the redesign of official observation procedures and policies of football governing bodies that are in charge in charge of referee's match evaluations.